Upaya Guru Bimbingan dan Konseling dalam Mengatasi Burnout Study Siswa di SMK Negeri 1 Tanjung Raya Kab. Agam - Aisyah Purnama Sari; Yeni Afrida (Lembaga Yasin AlSys, 2026)
Although study burnout has received increasing attention in the context of vocational secondary education, research specifically examining the efforts of guidance and counseling teachers to address it among Grade XI Computer and Network Engineering students remains relevant for further investigation. This study aimed to examine the efforts made by guidance and counseling teachers to overcome study burnout among Grade XI Computer and Network Engineering students at SMK Negeri 1 Tanjung Raya, Agam Regency. This study employed a qualitative method with a descriptive-qualitative approach. The research informants consisted of guidance and counseling teachers, homeroom teachers, and Grade XI Computer and Network Engineering students. Data were collected through interviews, observation, and documentation. The results showed that guidance and counseling teachers had undertaken various efforts to address study burnout, including providing motivation, delivering learning and information services, using engaging instructional media, and conducting group guidance services. These efforts contributed to reducing students’ study burnout. Thus, guidance and counseling teachers play an important role in helping students develop optimally. The implications of this study underscore the need for structured, collaborative, and innovative guidance and counseling services to be integrated sustainably into school programs in order to prevent and minimize study burnout, while supporting the creation of a conducive learning climate oriented toward students’ psychological well-being.